Differences between CD95 type I and type II cells detected with the CD95 ligand - Schmitz, Ingo; Walczak, Henning; Krammer, Peter H.; Peter, Marcus E. (Cell death and differentiation, 1999)
Reports on differences between CD95 type I and type II cells detected with the CD95 ligand. Member of the death receptor family; Apoptosis signaling pathways; Differences on the level of the death-inducing signaling complex.